THE PROTECTION OF NASCITURUS WITHIN THE CIVIL LAW - Simić, Jelena (Pravni zapisi, 2018)
Modern constitutions of civilized countries guarantee every person’s right to life, physical and mental integrity. Since constitutional norms guarantee the protection of "human" life, this led to the question: "At what point is "human" life considered to begin?" A grand majority of legal regulations is intended for people who are already born, which is why it is often questioned whether they are adequate for the unborn, i.e. what position contemporary legal systems occupy toward conceived and unborn human life. This paper attempts to answer the question whether the legal rule "he who causes damage must compensate for it" can be applied in case of a conceived and unborn person; i.e. if an embryo, considering that it has not become a legal subject, could claim the position of "other", i.e. a human?Analyzing the German legal theory and case law, the author concludes that the civil law protects nasciturus from harm inflicted on their body or health, so a positive answer to the question could be given only from the point of view that for the right to compensation it is of little consequence when the harmful event took place; rather, what matters is the fact that, due to the event, the child was born with defects that could be qualified as damage in terms of legal regulations concerning liability. Key words: nasciturus, civil law, legal personality, damage, legal capacity, liability.